Being a Christian in the Business World: The Challenge and the Promise - Williams, Oliver F. (Horizons, 1984)
What does it mean to be a Christian in today's business world? It is this question which provides the focus for a course I teach called "Modern Decision Making in the Christian Tradition." The course is designed for college juniors and seniors who are interested in exploring the implications of Christian faith for a professional life. Students are exposed to the flaws in Adam Smith's famous apology for the capitalist economy and offered an approach to working in the system and reforming it from a Christian standpoint.It has been my experience that most students in the course are serious about their Christian faith, that is, they go to church on Sunday and they strive to live the sort of life that they understand to be Christian. They are largely from good homes and have learned the value of friendship and love from dedicated parents. Most of them, however, have not been challenged to think through the implications of their Christian faith for their life in the business world or in the wider social order.While they may be models of compassion and generosity to those in their immediate circles, many students today have a blindspot for responsibilities in the socio-political order. In the traditional vocabulary, they are strong on charity but weak in justice. Justice in our time is often equated with "law and order," the quid pro quo's that insure that we each get what we deserve. One of the objectives of the course is to widen the horizons of the students so that they come to see more adequately what is entailed in calling oneself "Christian." To begin, I have them reflect on sections of "Justice in the World," the document issued by the Roman Synod of Bishops in 1971.